2020
DOI: 10.1037/tra0000581
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Brief Experiential Avoidance Questionnaire among treatment-seeking veterans with posttraumatic stress disorder.

Abstract: Objective: The present study aimed to explore the psychometric properties of the Brief Experiential Avoidance Questionnaire (BEAQ) among veterans seeking treatment for posttraumatic stress disorder (PTSD). Given that experiential avoidance (EA) is implicated in the development and maintenance of PTSD, it appears to be a possible clinical target for change across treatment. Method: The BEAQ was administered among two samples of military veterans seeking outpatient (n ϭ 179) and residential (n ϭ 257) treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Item 6 showed overall poor performances and was thus not included in the factor analyses. Our findings—alongside Byllesby et al’s (2020) who also found that Item 6 showed the lowest loadings in the one-factor CFAs in both clinical populations—would imply that Item 6 could potentially be removed from the BEAQ scoring. Its reverse item formulation may be problematic (Weijters et al, 2013) and future studies should investigate whether Item 6 should be retained in the BEAQ.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Item 6 showed overall poor performances and was thus not included in the factor analyses. Our findings—alongside Byllesby et al’s (2020) who also found that Item 6 showed the lowest loadings in the one-factor CFAs in both clinical populations—would imply that Item 6 could potentially be removed from the BEAQ scoring. Its reverse item formulation may be problematic (Weijters et al, 2013) and future studies should investigate whether Item 6 should be retained in the BEAQ.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, the BEAQ's factor structure was explored in two treatment seeking veteran samples (N = 179 and 257). The veterans in this study seemed considerably more avoidant (M = 66.7-68.8) than the samples in the original validation study (M = 52.02-56.41 for the patient samples and M = 43.33-49.37 for the nonclinical samples; Byllesby et al, 2020;Gámez et al, 2014). In the confirmatory factor analyses (CFA), the one-factor model fit was poor and three items did not significantly load on the factor (Items 4, 6, and 7 and Items 1, 3, and 6).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Fourth, we used the BEAQ to evaluate changes in EA, because it has been recommended over other widely-used measures due its excellent construct, convergent, and discriminant validity (Rochefort et al, 2018;Tyndall et al, 2019). However, the BEAQ has been criticized for 1) using items related to behavioral (vs. internal) avoidance (Tyndall et al, 2019), and 2) demonstrating poor fit in certain samples (e.g., treatment-seeking veterans; Byllesby et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%